Concepções implícitas de Pibidianos do curso de ciências da natureza: reflexões e desafios da formação docente - Gobbi, Cristiane Costa (2023)
Teachers' initial training aims to prepare them for the profession exercise, based on the act of learning and learning to teach, involving academic challenges and opportunities. Thus, this research aims to investigate the Implicit Conceptions of an undergraduate group of the Natural Sciences major regarding the teacher training challenges in the face of the teaching-learning process conceived from their participation in PIBID. It is characterized by being qualitative, with an interpretative, exploratory and descriptive bias, with an action research procedure. The setting was a public school in city of Uruguaiana/RS and the subjects of the study were ten Natural Science Pibidians and a research teacher working in the Science area of Secondary Education. The research included study, analysis, reflection and discussion based on theoretical material and the school's Pedagogical Political Project (PPP) ; in addition to studies and lectures on the National Common Curricular Base (BNCC). Reflective writing and questionnaires were used as collection instruments. Subsequently, the data were analyzed and treated according to the Content Analysis technique. The results revealed, for the authors of this systematic review, the importance of building an essential reflective behavior during the teacher training period. In identifying the Implicit Conceptions of Pibidianos, based on the PPP study, it has emerged the direct profile, which emphasizes the reproduction of knowledge with a focus on the teacher, and the constructive profile, which aims at the student's active participation. In relation to the implicit conception, after studying the BNCC, a significant number of constructive profiles were found, indicating the relevance of initial training based on the construction of new concepts that overlap implicit beliefs. Therefore, it can be stated that although a significant number of Pibidians fit into the constructive profile, there is a need to invest in understanding the teaching-learning processes to improve their teaching performance. In this sense, it can be stated that initial training is essential for changing the conception of implicit beliefs based on the connection between theory, practice and reflections.